The Influence of Digital Leadership on Organizational Performance in Jakarta - Nurshinta; Vira Deyana Cindy; Osly Usman, (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
Digital technology's transformative influence in business is undeniable, reshaping strategies and operations. Embracing this change goes beyond tech adoption it requires aligning culture, structure, and people with the evolving landscape. Digital leadership is crucial in navigating this realm, impacting job motivation, innovation, and overall performance. However, the relationship between digital leadership, employee performance, and digital culture is complex and context-dependent. The study aims to investigate the impact of digital leadership on organizational performance, with digital culture, digital technology, and digital marketing as intervening variables concerning sustainability and organizational performance in Jakarta. It uses a quantitative approach to analyze the numerical relationship between the variables. Utilizing a Purposive Sampling design, the Partial Least Square (PLS) approach will be employed for study analysis, with assistance from the SMARTPLS 4.0 application. Digital culture, marketing, and technology are all has significant influence by digital leadership. Higher digital leadership positively correlates with increased digital culture, marketing, and technology, while lower digital leadership negatively affects these aspects. Digital culture significantly influences organizational performance. Meanwhile, digital marketing shows a positive influence on performance but lacks significance. Digital technology positively and significantly affects organizational performance. Prioritize the enhancement of digital leadership to advance digital culture, marketing strategies, and technological implementation within organizations. Examine how digital culture contributes to organizational performance, emphasizing a culture fostering innovation, adaptability, and collaboration.